Antibacterial Activity Test of Ethanol Extract of Red Macroalgae (Acanthopora Spicifera) Against Staphylococcus Aureus Bacteria - Taibin, Ali; Yamin, Imam Syahputra; Nurul Furqan, Baiq Repika (Universitas Islam Negeri Mataram, 2022)
Bacterial infection Staphylococcus aureus has become a significant global health problem, mainly due to increasing resistance to existing antibiotics. To overcome this problem, research is continuing to find new sources of natural antibacterial agents. Red macroalgae (Acanthopora sp.) has promising biological potential, including activity as an antimicrobial. This study aims to determine the effect and how much concentration of red macroalgae ethanol extract (Acanthopora sp.) which is close to the value of the inhibition zone of the positive control Amoxicillin in inhibiting bacterial growth S. aureus. This research is a laboratory experimental research. The stages of the research began with taking red macroalgae samples (Acanthopora sp.) collected from Pandanan beach, North Lombok Regency, West Nusa Tenggara by the method simple random sampling and identified morphologically, manufacture of simplicia, manufacture of red macroalgae ethanol extract (Acanthopora sp.) with 99.99% ethanol solvent (absolute p.a), phytochemical screening tests, and antibacterial activity tests using a Completely Randomized Design (CRD) were carried out by well diffusion method with concentration variations of 2%, 4%, 6%, 8% and 10%, Amoxicillin as positive control and aquadest as negative control and ethanol as solvent control. Antibacterial activity test results from the crude extract of red macroalgae (Acanthopora sp.) against bacteria S. aureus incubated during overnight (16-18 hours) in an incubator with a temperature of 37OC. The results showed that the phytochemical analysis of the ethanol extract of red macroalgae identified the presence of flavonoids and saponins which are known to have potential as antibacterial agents. The presence of these compounds supports the antibacterial activity of red macroalgae against S. aureus. Red macroalgae ethanol extract (Acanthopora sp.) has antibacterial activity against S. aureus. The antibacterial activity of the ethanol extract showed a concentration-response pattern, where the higher the concentration of the extract, the greater the inhibition zone formed. The concentration of 10% ethanol extract showed the largest inhibition zone with an average diameter of 23.5 mm with the sensitive category.